Effective withdrawal of antiepileptic drugs in premonitoring admission to capture seizures during limited video‐EEG monitoring. Issue 2 (2nd March 2017) - Kagawa, Kota; Iida, Koji; Baba, Shiro; Hashizume, Akira; Katagiri, Masaya; Kurisu, Kaoru; Otsubo, Hiroshi
Summary: Objective: Withdrawal of antiepileptic drugs (AEDs) is commonly applied to capture seizures in video‐EEG (vEEG) monitoring for patients with infrequent but intractable seizures. Because of the half‐life of AEDs, AED withdrawal during only vEEG tends to be inadequate to provoke seizures within the vEEG admission. We hypothesize that prewithdrawal of long‐half‐life AEDs in premonitoring admission (PMA) is safe and effective to capture seizures in the limited time of vEEG. We determined the effect of half‐life on the interval between AED withdrawal and seizure occurrence. Methods: We collected 87 patients with three criteria: (1) seizure occurrence ≤3 per month; (2) AEDs ≥2; (3) AED withdrawal during their admission, among 126 consecutive patients who underwent vEEG in the Department of Neurosurgery, Hiroshima University Hospital between 2011 and 2014. We divided patients into two groups on the basis of half‐life of AED: Group A (23 patients) with phenobarbital (PB) and/or zonisamide (ZNS); Group B (64 patients) with other AEDs. In Group A, PB and ZNS were withdrawn during 4‐day PMA before vEEG started. Further AED withdrawal was performed during vEEG, depending on the seizure occurrence. Results: The number of AEDs on admission was significantly higher in Group A (2–6, 3.5 ± 0.9; range, mean ±SD) than in Group B (2–5, 2.8 ± 0.8) (p < 0.01). All 23 Group A patients and 13 (20%) Group B patients underwent AED withdrawal during PMA. Seizures occurred during PMA in two patients in both Group A (9%) and Group B (15%). The first seizure occurred significantly longer after the start of withdrawal in Group A (6.1 ± 2.0 days) than in Group B (2.8 ± 1.3 days) (p < 0.01). Seizures were equally captured between both groups: 96% in Group A and 92% in Group B during vEEG. Significance: For epilepsy patients who are treated with PB and/or ZNS, we recommend the planning of AED withdrawal during PMA before the start of vEEG to succeed in capturing seizures during the limited time of vEEG monitoring.